Impacto de las sanciones administrativas en la calidad del servicio de las Cooperativas de Transporte Interprovincial 2022-2023 - Orna Nogales, Carlos Geovanny (2024)
Interprovincial transport in Ecuador is key to economic development and regional connectivity. Transport cooperatives play a crucial role in mobility, but their quality of service can be affected by administrative sanctions imposed by regulatory authorities. These sanctions, which include fines, route suspension and revocation of permits, seek to ensure regulatory compliance and improve service safety. For this reason, the general objective was to analyze the impact of administrative sanctions imposed by the competent authorities on the quality of service offered by interprovincial transport cooperatives during the period 2022-2023. This mixed-approach, non-experimental descriptive research evaluated the impact of sanctions on quality indicators such as punctuality, safety, comfort and customer satisfaction. The sample, which included the highest authority of the provincial transit agency, cooperative operators and users, allowed the identification of perceptions and effects of the sanctions system, establishing among its conclusions that, although sanctions improve some aspects of the service, there is a perception that their application can be disproportionate and detrimental to the operation of the cooperatives.